Can complex visual discrimination deficits in amnesia be attributed to the medial temporal lobe? An investigation into the effects of medial temporal lobe damage on brain connectivity1. Issue 1 (31st July 2012) - Rudebeck, Sarah R.; Filippini, Nicola; Lee, Andy C.H.
Abstract It has been suggested that complex visual discrimination deficits in patients with medial temporal lobe (MTL) damage may be explained by damage or dysfunction beyond the MTL. We examined the resting functional networks and white matter connectivity of two amnesic patients who have consistently demonstrated discrimination impairments for complex object and/or spatial stimuli across a number of studies. Although exploratory analyses revealed some significant differences in comparison with neurologically healthy controls (more specifically in the patient with a larger MTL lesion), there were no obvious findings involving posterior occipital or posterior temporal regions, which can account entirely for their discrimination deficits. These findings converge with previous work to support the suggestion that the MTL does not subserve long‐term declarative memory exclusively. © 2012 Wiley Periodicals, Inc.